Fungsi Upacara Tae Mata Bagi Masyarakat Desa Wudi Kecamatan Cibal Kabupaten Manggarai NTT - Safitra Geong, Viani; ., Purwadi; Murniasih, A.A.Ayu (Humanis, 2016)
Tae mata ceremony is a funeral ceremony for the villagers Wudi Manggarai district . This ceremony consists of several important procession namely : haeng nai procession , Tekong mbakung , po , e woja agu latung , ici mu , u , dea ceki ,acem peti , boak , lonto walu , saung ta , a, pat puluh wie , and kelas . As the development time tae mata changing ceremony is on the procession samo lime, wero , saung ta , a, boak , and pat pulu h wi e . Tae Mata ceremony has a function that is part of the life cycle, the surviving family tribute to those who died, and to maintain safety for the families who are still alive . In addition to functioning. Tae Mata ceremony Mata also has a very important significance , namely : a religious meaning , the meaning of solidarity , the meaning of kinship , psychological meaning , and the meaning of education